Impact of sarcopenia on outcomes of patients undergoing liver resection for hepatocellular carcinoma. Issue 5 (19th July 2022) - Yang, Jinhuan; Chen, Kaiwen; Zheng, Chongming; Chen, Kaiyu; Lin, Jian; Meng, Qishan; Chen, Ziyan; Deng, Liming; Yu, Haitao; Deng, Tuo; Bo, Zhiyuan; He, Qikuan; et al.
Abstract: Background: Previous studies have indicated that sarcopenia is associated with poor post‐operative outcomes in liver cancer patients, but the studies are limited by confounding from mixed diseases, retrospective data, and non‐standardized measurement methods. At present, there is no research with both muscle mass and strength as predictors for hepatocellular carcinoma (HCC) outcomes. We studied the impact of sarcopenia on post‐operative outcomes in HCC patients in a cohort study designed according to the European Working Group on Sarcopenia in Older People standards. Methods: A total of 781 consecutive patients admitted to our centre were registered from May 2020 to August 2021. All participants submitted questionnaires and underwent handgrip strength, chair stand test, physical performance, and computed tomographic evaluation. Then, they were divided into three groups according to muscle mass and strength: Group A (reduced muscle mass and strength), Group B (reduced muscle strength or reduced muscle mass), and Group C (normal muscle mass and strength). The baseline data and post‐operative outcomes were compared and analysed. The primary outcome variable in this study was the presence of a major post‐operative complication, and the secondary outcome was the 90‐day re‐admission rate. Results: A total of 155 patients [median age, 60.00 (IQR, 51.00–66.00) years; 20 females (12.90%)] were included after strict exclusion. The mean (SD) BMI was 23.37 ± 0.23 kg/m 2 . The mean (SD) SMI of all participants was 47.05 ± 0.79 cm 2 /m 2, and the mean (SD) handgrip strength was 32.84 ± 0.69 kg. Among them, 77 (49.68%) patients underwent laparoscopic hepatectomy, and 73 (47.10%) patients received major hepatectomy. Regarding the post‐operative results, Group A had a higher rate of major complications [40.91% (9 of 22) vs. 11.94% (8 of 67) in Group B and 6.06 (4 of 66) in Group C; P = 0.001], higher rate of blood transfusion (77.27% vs. 46.27% in Group B and 42.42% in Group C; P = 0.015), higher hospitalization expenses ( P = 0.001), and longer hospital stay ( P < 0.001). There was no difference in 90‐day re‐admission rates among the three groups. Sarcopenia (hazard ratio, 10.735; 95% CI, 2.547–45.244; P = 0.001) and open surgery (hazard ratio, 4.528; 95% CI, 1.425–14.387; P = 0.010) were independent risk factors associated with major complications. Conclusions: Sarcopenia is associated with adverse outcomes after liver resection for HCC. It should be evaluated upon admission to classify high‐risk patients and reduce the risk of major complications.